Sex differentiation of the European eel in brackish and freshwater environments: a comparative analysis - Melià, Paco; Bevacqua, Danièle; Crivelli, Alain Jean; Panfili, Jacques; De Leo, Giulio Alessandro; Gatto, Marino (Journal of Fish Biology, 2006)
International audience Body growth parameters, age and total length at sex differentiation were compared in three European eel Anguilla anguilla populations from Mediterranean sites with different salinity. Whilst body growth was faster in brackish than in freshwater environments, the present analysis shows that body size at sex differentiation might be a physiological invariant.